Diagnostic and Prognostic Value of Dysregulated miR-10a-3p in Patients with Severe Pneumonia - Xie J; Li Y; Wang M; He W; Zhao X (Dove Medical Press, 2022)
Jianwan Xie,1,* Yanchu Li,1,* Man Wang,2,* Wenping He,3 Xinxin Zhao1 1Department of Geriatric Medicine, Xuzhou No.1 People's Hospital, Xuzhou, 221002, People's Republic of China; 2Medical Oncology, Xuzhou No.1 People's Hospital, Xuzhou, 221002, People's Republic of China; 3Department of Pharmacy, Xuzhou No.1 People's Hospital, Xuzhou, 221002, People's Republic of China*These authors contributed equally to this workCorrespondence: Xinxin Zhao, Department of Geriatric Medicine, Xuzhou No.1 People's Hospital, 269 University Road, Xuzhou, 221002, People's Republic of China, Tel/Fax +86-0516-962011, Email zhaoxx1985@163.com Wenping He, Department of Pharmacy, Xuzhou No.1 People's Hospital, 269 University Road, Xuzhou, 221002, People's Republic of China, Email hei33822lai@163.comPurpose: Previous studies have shown that microRNA is involved in regulating a variety of human inflammatory diseases. The purpose of this study was to investigate the expression of miR-10a-3p in the blood of patients with severe pneumonia and evaluate its value in the diagnosis and prognosis of severe pneumonia.Patients and Methods: Seventy patients with severe pneumonia and 75 healthy individuals were included in this study. Venous blood of all subjects was obtained for RT-qPCR analysis to obtain the relative expression level of miR-10a-5p. The diagnostic accuracy of miR-10a-5p for severe pneumonia was assessed by ROC curve. After standardized treatment, the prognosis of patients with severe pneumonia was analyzed by a 28-day follow-up method. Kaplan-Meier curve and multivariate Cox regression analysis were used to determine the basic factors influencing the prognosis of patients.Results: Compared with healthy control, serum miR-10a-3p expression in patients with severe pneumonia was distinctly upregulated (P < 0.001). Besides, ROC analysis showed that miR-10a-3p had high diagnostic accuracy for severe pneumonia, with an AUC of 0.881, sensitivity and specificity of 75.7% and 84.0%, respectively. Kaplan-Meier curve exhibited that high miR-10a-3p expression group had a higher probability of death than those with low miR-10a-3p expression. Multivariate Cox regression analysis demonstrated that miR-10a-3p and CRP were independent risk factors affecting the prognosis of patients.Conclusion: The expression of miR-10a-3p was increased in patients with severe pneumonia, and abnormally expressed miR-10a-3p has the potential to be used as a diagnostic and prognostic marker for severe pneumonia, which provides a new biological direction for the early detection and risk assessment of severe pneumonia.Keywords: severe pneumonia, miR-10a-3p, diagnosis, prognosis